Immunolocalization and protein expression of the alpha subunit of the large-conductance calcium-activated potassium channel in human myometrium - Chanrachakul, B; Matharoo-Ball, B; Turner, A; Robinson, G; Broughton-Pipkin, F; Arulkumaran, S; Khan, R N (Reproduction (Cambridge, England), 2003)
Large-conductance calcium-activated potassium (BKCa) channels play an important role in the control of myometrial excitability. The aim of the present study was to determine the localization and protein expression of the alpha subunit of BKCa channels in the pregnant and parturient human uterus. An anti-alpha BKCa channel monoclonal antibody (anti-alpha(995-1113)) was used to localize and quantitate immunoreactive BKCa channel protein in myometrium of singleton term pregnant women undergoing either elective (n=26) or emergency Caesarean section following the onset of spontaneous labour (n=25). Data are presented as medians (interquartile range). Differences between groups were analysed using the Mann-Whitney U test. Immunohistochemistry studies localized the alpha subunit of the BKCa channel to the plasma membrane and the cytosol of myometrial cells with similar reaction end product in pregnant women who were or were not undergoing labour. Expression of this subunit, observed as a 125 kDa band in western blots, was significantly higher in pregnant women who were not undergoing labour (30.6% (20.3, 43.9)) than in those who were undergoing labour (15.7% (11.3, 22.4); P<0.01). Reduced BKCa alpha subunit expression in pregnant women during labour may underlie the initiation of uterine contractility during parturition.